Diet and nutrition strategies for cancer prevention: A comprehensive review - Hinduja, Divya Bharathi; Dhanu, A. S.; Swamy, G. G.; Murugesan, Karthikeyan; Elango, Boojhana; Murali, Uthamalingam; Rashid, Mamunur; Mathanmohun, Maghimaa; Basalingappa, Kanthesh M. (Research in Biotechnology, 2023)
Maintaining a healthy diet is crucial for preventing cancer, as it provides the essential nutrients needed for proper physiological functioning. It is predicted that simple lifestyle and dietary changes can lessen the risk of developing 30-40% of all malignancies. Obesity, the consumption of nutrient-deficient foods such as sugary and refined flour products, which can lead to impaired glucose metabolism and, eventually, diabetes, a lack of dietary fiber, an excess of red meat, and an imbalance in the consumption of omega-3 and omega-6 fats are all risk factors for cancer. To reduce your risk of cancer, include flax seeds, a variety of fruits and vegetables, and dietary fiber in your diet. Additionally, there is proof that nutritional supplements may help lower the risk of breast cancer recurrence. To prevent various types of cancer, it is important to include vegetables, fruits, whole grains, and specific fatty acids in your diet, alongside engaging in regular physical exercise. Furthermore, it is crucial to use advances in genetics and molecular biology to extend nutritional research from observational studies to demonstrating causative linkages. Cancer prevention strategies that involve dietary changes targeted at specific groups should be based on a thorough understanding of these fundamental principles. Such dietary methods can be effective as well as in cancer prevention but also cancer rehabilitation. This review investigates the relationship between cancer and diet, examines straightforward approaches to incorporating cancer-preventive foods into one’s diet, investigates the impact of dietary variables and lifestyle choices on the risk of cancer, and investigates clinical studies focused on nutrition and cancer prevention.